(untitled) (LACCEI, 2024)
WebLab, Lab-on-Web, or e-science means access to real labs and devices through the Internet. The goal is to enable interactivity with devices, control and monitoring, and cooperative work. Therefore, this work aims to present the DistLab, a distillation column that was adapted for batch operation remotely, attending the demands of Education 4.0. A distillation column is used to separate components from a liquid mixture by volatility difference and it is applied to many industrial processes. Thus, the engineering courses, will have a product at the service of the academic community that will allow remote access to the distillation experiments. In the present study, four experiments were performed in order to stablish operational parameters for safe remote operation, which soon will integrate to the WebLab platform in which the project is integrated